Survey of sheep and goat producers in Costa Rica: perspectives, risks, and health challenges in the sector - Soto-Barrientos, Natalia (2024)
Even though sheep and goat production has progressively grown in Costa Rica in the last few years, the information about these production systems is still scarce and imprecise. Consequently, a survey was conducted of 100 farms (64 goat farms and 36 sheep farms) to carry out a baseline diagnosis of Costa Rican sheep and goat production systems, mainly regarding nutritional, reproductive, and sanitary management. Almost all goat herds are dedicated to milk production, with an average of 17 adult females per herd, while all sheep herds are dedicated to meat production, with an average of 55 females. A frequent use of confined (52%) or semi-confined (51%) systems was observed, as well as a lower frequency of extensive grazing (28%). The average age of the producers surveyed was 45 years, with an average experience in the activity of 8.8 years. A total of 69% of producers have at least a level higher than secondary education. Most farms (88%) maintain some manual or digital record. A total of 91% of herds use natural mating with the farm’s males. The survey revealed essential deficiencies in biosafety and health management. Potential health risks were also detected. The most frequently reported health problems in the herds were abortions and calving problems, as well as respiratory problems, diarrhea, and lameness. A significant positive association was evident between biosafety risks and the prevalence of health problems. These findings offer an essential perspective to shape future policies and actions to promote the development and sustainability of the livestock industry in the country.